Biological control affects native vegetation and recovery potential in Theodore Roosevelt National Park, North Dakota - Laufmann, Julie Ann, author; Trlica, M. J., advisor; Butler, Jack L., advisor; Wiesner, Loren E., committee member; Uresk, Daniel W., committee member (Colorado State University. Libraries, 2006)
This study evaluated native vegetation recovery in areas infested with leafy spurge (Euphorbia esula L.) and treated with the bio-control agent Aphthona spp. and examined in-situ seed bank potential to predict recovery of native species. Extant vegetation and seed bank species richness, diversity, composition and community similarities were evaluated in leafy spurge infested, infested leafy spurge sites that received bio-control treatment, and non-infested sites in three vegetation associations in the South Unit of Theodore Roosevelt National Park, North Dakota. The Modified Whitaker sampling method was used to obtain extant species richness and relative cover. Seed bank sampling plots (15 m x 15 m) were centered in the Modified Whitaker plots. Similarity and dissimilarity analyses compared species assemblages among non-infested, infested and bio-control sites in extant vegetation, seed banks, and between extant vegetation and seed bank species. No reductions in extant species richness or diversity were observed between non-infested, infested, and bio-control sites across the three vegetation associations (p ≥ 0.05). Extant vegetation forb component was reduced by 13-30% in bio-control sites compared to non-infested sites. Eighty-nine percent of extant species affected by leafy spurge infestation were present in bio-control sites. Similarity coefficients between extant vegetation and seed bank species were low, reflecting heterogeneity of badlands topography. Seed was present in bio-control and infested sites for 50 to 75% of commonly occurring extant vegetation species documented in non-infested sites across the vegetation associations. Mean leafy spurge seed densities in infested sites ranged between 447 to 931 seed/m2 in and 164 to 724 seed/m2 in bio-control sites across vegetation associations. Leafy spurge seed densities in infested sites were not significantly different than those observed in bio-control sites. Non-native species seed densities other than leafy spurge were similar among sites. Vegetation previously infested by leafy spurge and treated with bio-control agents are recovering in the Park and will continue to improve based on the presence of seed bank species. Future monitoring of impacted areas is necessary to validate results to ensure that leafy spurge does not re-establish in communities because of high seed densities of leafy spurge seed in bio-control sites.
Keywords: range management; environmental science